Embodied Knowing: An Experiential, Contextual, and Reflective Process - Mimi Sodhi (Adult Education Research Conference, 2008)
This study explored the process of embodied knowing in social workers. Analysis of data gathered through interviews with ten participants revealed embodied knowing to be a developmental process based on experience, context, and reflection.
Keywords: embodied knowledge; bodily knowing